2023
DOI: 10.1177/11786361221150760
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Multi-Drug Resistant Salmonella typhi Isolated From Blood Sample

Abstract: Typhoid is a major public health concern. Even though antibiotics are usually used to treat typhoid fever, the spread of multi drug resistant Salmonella typhi is making antibiotics much less effective. This study was conducted to assess the prevalence of multidrug-resistant Salmonella typhi from the clinical samples. During this study, 154 blood samples of suspected typhoid patients were collected from the hospital and diagnostic center located in Chattogram City, Bangladesh. Isolation and identification of Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…A high prevalence (44.87%) of MDR non-typhoidal Salmonella isolates was also observed in our study. This finding is consistent with the results of a previous study on various host species in the United States [79] but lower than the prevalence found in MDR S. strains isolated from blood samples in Chattogram City, Bangladesh [80]. The difference may relate to the abuse of drugs in the poultry breeding industry.…”
Section: Discussionsupporting
confidence: 92%
“…A high prevalence (44.87%) of MDR non-typhoidal Salmonella isolates was also observed in our study. This finding is consistent with the results of a previous study on various host species in the United States [79] but lower than the prevalence found in MDR S. strains isolated from blood samples in Chattogram City, Bangladesh [80]. The difference may relate to the abuse of drugs in the poultry breeding industry.…”
Section: Discussionsupporting
confidence: 92%
“…This study used the boiling method to isolate bacterial DNA [ 22 , 23 ]. After purity and DNA concentration check through NanoDrop, highly purified and concentrated DNA samples were selected for PCR amplification and stored at -20°C.…”
Section: Methodsmentioning
confidence: 99%
“…They are generally associated with tetAR, strAB and sul2, although other antibiotic-resistance genes have been identified (McMillan et al, 2020;Oliva et al, 2017;Poirel et al, 2010). In Bangladesh, recently reported clinical isolates of MDR S. Typhi showed higher resistance to nalidixic acid compared to other antibiotics (Mina et al, 2023). Reports from 2014 to 2018 showed that MDR S. Typhi and Paratyphi A possessed non-conjugative non-IncHI1 plasmids and multiple gene markers of AMR such as bla TEM-1 , catA, sul1, sul2, dfrA15 (Dutta et al, 2014;Samajpati et al, 2020).…”
Section: Mechanisms Of Multidrug Resistance (Mdr)mentioning
confidence: 99%
“…In Bangladesh, recently reported clinical isolates of MDR S . Typhi showed higher resistance to nalidixic acid compared to other antibiotics (Mina et al., 2023). Reports from 2014 to 2018 showed that MDR S .…”
Section: Mechanisms Of Drug Resistance In Salmonellamentioning
confidence: 99%